2003
DOI: 10.1088/0953-4075/36/19/001
|View full text |Cite
|
Sign up to set email alerts
|

Alignment following Au L3photoionization by synchrotron radiation

Abstract: The alignment of Au + ions following L 3 photoionization has been studied using a high-resolution x-ray spectrometer. We observed a small anisotropy for the angular dependence of Au L ι and Lα emissions. The alignment parameter A 20 derived from the experimental results is compared with theoretical calculations by Hartree-Fock approximation and random phase approximation with exchange. The contribution to the alignment of quadrupole interaction is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…They reported a maximum anisotropy of 5% of the Lα line with an instrumentation having a relative uncertainty of already 2% in the case of an isotropic emission characteristic. However, Yamaoka et al had also studied the angular distribution of Au L fluorescence lines following photoionization by monochromatized synchrotron radiation with energies in the vicinity of the L subshells [34,35]. They had found that in the case of the Au Ll fluorescence line an anisotropy of just a few percent might be possible, whereas the expected anisotropy of the Lα lines should be at least one order of magnitude lower, thus being somewhere in the per mille range which is not in line with some of the later findings [33] despite the undisputable fact that both works are based on the same theoretical considerations of Berezhko et al [36].…”
Section: Resultsmentioning
confidence: 99%
“…They reported a maximum anisotropy of 5% of the Lα line with an instrumentation having a relative uncertainty of already 2% in the case of an isotropic emission characteristic. However, Yamaoka et al had also studied the angular distribution of Au L fluorescence lines following photoionization by monochromatized synchrotron radiation with energies in the vicinity of the L subshells [34,35]. They had found that in the case of the Au Ll fluorescence line an anisotropy of just a few percent might be possible, whereas the expected anisotropy of the Lα lines should be at least one order of magnitude lower, thus being somewhere in the per mille range which is not in line with some of the later findings [33] despite the undisputable fact that both works are based on the same theoretical considerations of Berezhko et al [36].…”
Section: Resultsmentioning
confidence: 99%
“…Several groups published the results of measurements of the angular anisotropy of X-ray fluorescence, in which the 2p vacancies in heavy atoms have been created by radiation from radionuclides (see Santra et al, 2007 and references therein). Unusually large anisotropy as well as large forward-backward asymmetry have been reported in some of those experiments (see discussion in Yamaoka et al, 2002Yamaoka et al, , 2003Santra et al, 2007 and references therein) in drastic disagreement with the theoretical predictions. Recent, more precise and accurate measurements at SR sources, showed a very small anisotropy of L X-ray lines (Küst et al, 2003;Yamaoka et al, 2003Yamaoka et al, , 2006Barrea et al, 2005) in complete agreement with the theoretical predictions.…”
Section: Alignment and Orientation In The Direct Photoionization Of Amentioning
confidence: 94%
“…Unusually large anisotropy as well as large forward-backward asymmetry have been reported in some of those experiments (see discussion in Yamaoka et al, 2002Yamaoka et al, , 2003Santra et al, 2007 and references therein) in drastic disagreement with the theoretical predictions. Recent, more precise and accurate measurements at SR sources, showed a very small anisotropy of L X-ray lines (Küst et al, 2003;Yamaoka et al, 2003Yamaoka et al, , 2006Barrea et al, 2005) in complete agreement with the theoretical predictions. As it was suspected, the measurements with the radionuclides, which were interpreted as showing large alignment, contained some large systematic errors probably connected with self-absorption of the produced X-rays in the solid target.…”
Section: Alignment and Orientation In The Direct Photoionization Of Amentioning
confidence: 94%
See 1 more Smart Citation
“…Up to now, many experimental studies related with the angular distribution of the L 3 (J = 3/2) magnetic subshell X-ray transitions using different stimulating sources, such as synchrotron radiation [6][7][8], X-ray tube [9], radioisotope sources [10][11][12][13][14][15][16][17][18], and with charged particles [19][20][21][22][23][24] have been done.…”
Section: Introductionmentioning
confidence: 99%